Supervisi Akademik Kepala Sekolah pada Kinerja Guru di SD Negeri Larangan Kabupaten Pati - Rina Andarwati; Nur Fajrie; Sri Surachmi W (Departement of Mathematics Education, 2023)
This study aims to obtain information about the implementation of academic supervision in order to improve teacher performance by the principal. This research used qualitative method. Data were collected through interview, observation and documentation. The subjects of this research were the headmaster and the teachers. The results showed that the implementation of the academic supervision was done on three steps were planning, implementation and evaluation. The teachers gave positive responses to the implementation of academic supervision. The research method uses a qualitavie descriptive approach. Data was collected informants, namely school principals, teachers and school supervisors, documents and events related to the school principal at SDN Larangan, Tambakromo District. Methods of data collection Interview, observation and documentation. Data analysis techniques through the stages of data collection, data reduction, presentation and inference. The results of this study indicate that principal”s academic supervision in accordance with applicable regulations. The principal plans, implements, evaluates and monitors the results of controlling leraning to achieve qulity teaching. In addition, the application of good academic leadership by school principals can create cohesiveness between educators and education staff to improve the learning process